Simulations and Analyses of Expected Nucleon Transversity Measurements in the MINERvA Neutrino Experiment - Kehayias, Pauli. (Tufts Archival Research Center, 2005)
Coherent charged current single pion production events were simulated and analyzed for the MINERvA neutrino experiment. The differential cross section of this reaction is transversity-dependent in the pion azimuthal angle phi according to two models: the GPD model and the Regge model. Our goal was to determine whether MINERvA will be able to differentiate between these two models. We found that the GPD model predicts an event rate largely independent of phi while the Regge model predicts a significant cos(2 phi) contribution. MINERvA will have sufficient resolution and statistics to distinguish between the two, though a more thorough investigation is needed.